AKTIVISME GREENPEACE DALAM MENDORONG PERUSAHAAN SHELL BERKONTRIBUSI PADA PERJANJIAN PARIS - Nazlatunnuha, Dinda Fitri (Indonesian Association for International Relations, 2024)
This research examines Greenpeace's activism in encouraging the Shell company to contribute to the 2015 Paris Agreement, and the power of Greenpeace as an INGO in that case. Through the concept of the main function of non-governmental organizations according to Glasius, Kaldor, and Anheier as an analytical tool as well as the concept of the power of non-governmental organizations according to BostrÃ¶m & HallstrÃ¶m. This research is described using descriptive and qualitative methods, as well as documentation studies which produce the argument that Greenpeace carries out its function as activism which acts as an